Mechanical ventilation and lung infection in the genesis of air-space enlargement - Sartorius, Alfonso (2007)
Introduction Air-space enlargement may result from mechanical ventilation and/or lung infection. The aim of this study was to assess how mechanical ventilation and lung infection influence the genesis of bronchiolar and alveolar distention. Methods Four groups of piglets were studied: non-ventilatednon- inoculated (controls, n = 5), non-ventilated-inoculated (n = 6), ventilated-non-inoculated (n = 6), and ventilated-inoculated (n = 8) piglets. The respiratory tract of intubated piglets was inoculated with a highly concentrated solution of Escherichia coli. Mechanical ventilation was maintained during 60 hours with a tidal volume of 15 ml/kg and zero positive end-expiratory pressure. After sacrifice by exsanguination, lungs were fixed for histological and lung morphometry analyses. Results Lung infection was present in all inoculated piglets and in five of the six ventilated-non-inoculated piglets. Mean alveolar and mean bronchiolar areas, measured using an analyzer computer system connected through a high-resolution color camera to an optical microscope, were significantly increased in non-ventilated-inoculated animals (+16% and +11%, respectively, compared to controls), in ventilated-non-inoculated animals (+49% and +49%, respectively, compared to controls), and in ventilated-inoculated animals (+95% and +118%, respectively, compared to controls). Mean alveolar and mean bronchiolar areas significantly correlated with the extension of lung infection (R = 0.50, p < 0.01 and R = 0.67, p < 0.001, respectively). Conclusion Lung infection induces bronchiolar and alveolar distention. Mechanical ventilation induces secondary lung infection and is associated with further air-space enlargement. The combination of primary lung infection and mechanical ventilation markedly increases air-space enlargement, the degree of which depends on the severity and extension of lung infection.